Development and Validation of an Instrument for Assessing Student´s Attitudes Towards the Use of Video-based Media in Physical Education - Beege, Maik; Roth, Anne-Christin; Bergmann, Jana; Schröder, Britta (Physical Education Theory and Methodology, 2025)
Background. The integration of digital media, particularly video-based technologies, has become an important element of contemporary education. While teachers’ attitudes toward digital media are well researched, students’ attitudes toward the use of video in physical education remain underexplored. Existing instruments capture only selected components of attitudes and do not fully represent the cognitive, affective, and behavioral structure. Therefore, a validated and comprehensive instrument is needed to assess students’ attitudes toward video-based media in PE. Objectives. To develop, refine, and validate a questionnaire measuring students’ attitudes toward the use of video-based media in physical education, based on an extended Technology Acceptance Model (TAM). Materials and Methods. The initial questionnaire consisted of 33 items covering cognitive, affective, and behavioral attitude components. A sample of 202 eighth-grade students (M = 13.26; SD = 0.54) participated. A series of confirmatory factor analyses (CFA) was conducted to optimize the factor structure. Internal consistency (ω, α), factor loadings, model fit indicators (CFI, RMSEA), and convergent/discriminant validity were evaluated. Results. The final scale includes 21 items forming a three-component structure: cognitive (ω = .74), affective (ω = .81), and behavioral (ω = .87). The factor model demonstrated acceptable fit (CFI = .82; RMSEA = .10). Significant correlations among subcomponents confirmed convergent validity, while the absence of substantial associations with demographic characteristics supported discriminant validity. Conclusions. The developed scale is a reliable and valid instrument for comprehensively measuring students’ attitudes toward the use of video-based media in physical education. It can be applied in future research on technology acceptance and in designing pedagogical interventions aimed at optimizing the use of video in PE lessons.